6p-1+p=8p-8

Simple and best practice solution for 6p-1+p=8p-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p-1+p=8p-8 equation:



6p-1+p=8p-8
We move all terms to the left:
6p-1+p-(8p-8)=0
We add all the numbers together, and all the variables
7p-(8p-8)-1=0
We get rid of parentheses
7p-8p+8-1=0
We add all the numbers together, and all the variables
-1p+7=0
We move all terms containing p to the left, all other terms to the right
-p=-7
p=-7/-1
p=+7

See similar equations:

| 6x+5=221 | | -7(1+3x)+7=-7-7(6x+8) | | 5k+3+8k=16 | | 5(-3v-8)=23-8v | | 7y=74 | | 5(x-12)=x-12 | | 4(-2y+10)=40 | | -6=y-13 | | 22+54x=-20x+60x | | -3s+3=-8-10s-10 | | 625x8=5000 | | 7x2+10=0 | | 143h+2=2 | | 6-y/4=1 | | 7x+10=3x+13 | | y+5y-8+4=5y+y-9+6 | | -z+3.26=15.3z | | 3+4y=y-9 | | 0.4(4t+7)=0.16(t+1)+0.12 | | 4x–4=40 | | 184x−3=72x+154 | | 2x+1-x-5=40 | | 49/12=56/x | | 5(x-12=x-12 | | 3/7=x/1 | | 2/5x-1=14 | | –3x+11=x–5 | | 8x²-15x=0 | | 2m+15=39 | | x3+-6x2+8x=0 | | -1.3x+5.2=1-2.7 | | 2(1-p)=5-p |

Equations solver categories